Tingkat pengetahuan, sikap dan perilaku ibu dalam pemberian imunisasi MR (Measles Rubella) pada anak usia 9 bulan–5 tahun - Umi Romayati Keswara; Eriyani Eriyani; Super Adinata (Holistik Jurnal Kesehatan, 2020)
Measles Rubella vaccine in children ages 6 to 60 months related knowledge, attitudes and practices of mothers in Lampung-IndonesiaBackground: Rubella is an acute and minor disease that often infects vulnerable children and young adults. High coverage and evenly at least 95% will create herd immunity and break the chain of rubella's spreading. Achievement of immunization obtained by UPTD in Puskesmas Margodadi was still low at 94.3%.Purpose: Knowing Measles Rubella vaccine in children ages 6 to 60 months related knowledge, attitudes and practices of mothers in Lampung-Indonesia.Method: This study was quantitative with a case-control design with populations in this study were mothers who had children aged 9-60 months  who were targeted in the implementation of mass MR immunization with a sample of 80 from 4 integrated service post or posyandu taken by Propositional Sampling. The instrument used was a questionnaire to determine the knowledge, attitudes, and behaviors of mothers in the provision of MR immunization. Data analysis used Chi-Square.Results: Distribution frequency of characteristics of mothers who didn’t give MR immunization with good knowledge were 18 respondents (45%) and not so good knowledge were 22 respondents (55%), distribution frequency of mothers with a positive attitude but not giving MR immunization were 17 respondents (42 , 5%) and negative attitude mothers were 23 respondents (57.5%). Chi-Square analysis showed that there was correlation between knowledge and mother's behavior with p value0.012 and there was correlation between attitudes and mother's with p value of 0.025.Conclusion: There were correlation of Measles Rubella vaccine in children ages 6 to 60 months related knowledge, attitudes and practices of mothers in Lampung-Indonesia. Suggestions for further research are to pay attention to predisposing factors, enabling factors, and reinforcing factors in their research.Keywords: Measles Rubella vaccine; Children; Mothers; Knowledge; Attitude; PracticesPendahuluan: Rubella merupakan penyakit akut dan ringan yang sering menginfeksi anak dan dewasa muda yang rentan. Cakupan yang tinggi dan merata minimal 95% akan membentuk herd immunity dan memutus rantai penularan penyakit rubella. Capaian imunisasi didapatkan UPTD Peskesmas Margodadi belum mencapai cakupan minimal sebesar 94,3%.Tujuan: Diketahui hubungan tingkat pengetahuan dan sikap terhadap perilaku ibu dalam pemberian imunisasi MR (Measles Rubella).Metode: Jenis penelitian kuantitatif dengan desain case-control, populasinya ibu yang memiliki anak usia 9 bulan–5 tahun yang menjadi sasaran dalam pelaksanaan imunisasi MR massal, dengan sampel 80 dari 4 posyandu yang diambil dengan cara proposional sampling. Instrumen yang digunakan berupa kuisioner untuk mengetahui pengetahuan, sikap, dan Perilaku ibu dalam pemberian imunisasi MR. Analisis data menggunakan Chi-Square. Hasil: Distribusi frekuensi karakteristik ibu yang tidak memberikan imunisasi MR dengan pengetahuan baik sebesar 18 responden (45 %) dan yang buruk sebesar 22 responden (55%), Distribusi frekuensi ibu dengan sikap positif namun tidak memberikan imunisasi MR sebesar 17 responden (42,5 %) dan ibu yang bersikap negatif sebesar 23 responden (57,5%). Uji analisis Chi-Square terdapat hubungan pengetahuan dengan perilaku ibu dengan ρ-value sebesar 0,012 dan terdapat hubungan sikap dengan perilaku ibu dengan ρ-value sebesar 0,025.Simpulan: Ada hubungan tingkat pengetahuan dan sikap dengan perilaku ibu dalam pemberian imunisasi MR. Saran peneliti selanjutnya agar tetap memperhatikan factor predisposisi, factor pemungkin, dan factor penguat dalam penelitiannya.